Eigil Rothe, an early twentieth century wall paintings conservator in Denmark - Isabelle Brajer (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Eigil Rothe (active 1897-1929) is a central figure in the development of wall paintings conservation and restoration in Denmark, marking a clear departure from the practices of artist-restorers influenced by historicism. His ideas about retouching and impregnation were propelled by his sense of aesthetics, which rejected nineteenth century interpretations, and called for a respect for the passage of time. His experiments with surface treatments demonstrate unprecedented thoughts about the necessity of future treatments. His work was driven by an aspiration for the truth, as seen by his diligent photographs, such as his noteworthy documentation of the stage prior to aesthetic treatment.